2018
DOI: 10.1667/rr14863.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Gamma-Ray ExposureIn Uteroin B6C3F1 Mice on Gestation Day 18 and at 10 Weeks of Age

Abstract: Pregnant C57BL/6JJcl mice were exposed to γ rays at low dose rate (20 mGy/day, LDR) or medium dose rate (200 and 400 mGy/day, MDR) from gestation day (GD) 0-18 to total accumulated doses of 360, 3,600 and 7,200 mGy, respectively. An additional group of pregnant mice were acutely exposed to 2 Gy at high dose rate (HDR) of 0.77 Gy/min on GD 11. In experiment 1, fetuses collected via cesarean section on GD 18 were examined for external and skeletal abnormalities. While the results of LDR exposure (20 mGy/day) did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…We elected to use B6C3F1 mice for this study since our previously reported studies (11,34,35) also used the same strain for comparison purposes. Experiments are also underway to study the late effects, such as life span and neoplasm incidence, of chronic exposure to gamma rays in utero under similar conditions using the same strain.…”
Section: Justification For the Use Of B6c3f1 Fetusesmentioning
confidence: 99%
See 4 more Smart Citations
“…We elected to use B6C3F1 mice for this study since our previously reported studies (11,34,35) also used the same strain for comparison purposes. Experiments are also underway to study the late effects, such as life span and neoplasm incidence, of chronic exposure to gamma rays in utero under similar conditions using the same strain.…”
Section: Justification For the Use Of B6c3f1 Fetusesmentioning
confidence: 99%
“…Pregnant dams were randomly assigned to groups receiving wholebody gamma-ray irradiation continuously for 22 h each day from GD 0 to 18 at a LDR (20 mGy/day, total dose ¼ 360 mGy) or at MDRs (200 mGy/day, total dose ¼ 3,600 mGy or 400 mGy/day, total dose ¼ 7,200 mGy) as described elsewhere (11). The remaining 2 h were used for health monitoring of the mice and husbandry procedures, such as cleaning the rooms, cage changes with fresh bedding and providing a fresh supply of food and water.…”
Section: Irradiationsmentioning
confidence: 99%
See 3 more Smart Citations